Vitrectomy for the removal of idiopathic epiretinal membrane with or without internal limiting membrane peeling: a meta-analysis - Christodoulou, Eleni (Ther Adv Ophthalmol, 2020)
PURPOSE: The aim of this study is to analyze the effect of internal limiting membrane peeling in removal of idiopathic epiretinal membranes through meta-analysis. METHODS: We searched PubMed for studies published until 30 April 2018. Inclusion criteria included cases of idiopathic epiretinal membranes, treated with vitrectomy with or without internal limiting membrane peeling. Exclusion criteria consisted of coexisting retinal pathologies and use of indocyanine green to stain the internal limiting membrane. Sixteen studies were included in our meta-analysis. We compared the results of surgical removal of epiretinal membrane, with or without internal limiting membrane peeling, in terms of best-corrected visual acuity and anatomical restoration of the macula (central foveal thickness). Studies or subgroups of patients who had indocyanine green used as an internal limiting membrane stain were excluded from the study, due to evidence of its toxicity to the retina. RESULTS: Regarding best-corrected visual acuity levels, the overall mean difference was –0.29 (95% confidence interval: –0.319 to –0.261), while for patients with internal limiting membrane peeling was –0.289 (95% confidence interval: –0.334 to –0.244) and for patients without internal limiting membrane peeling was –0.282 (95% confidence interval: –0.34 to –0.225). Regarding central foveal thickness levels, the overall mean difference was –117.22 (95% confidence interval: –136.70 to –97.74), while for patients with internal limiting membrane peeling was –121.08 (95% confidence interval: –151.12 to –91.03) and for patients without internal limiting membrane peeling was –105.34 (95% confidence interval: –119.47 to –96.21). CONCLUSION: Vitrectomy for the removal of epiretinal membrane combined with internal limiting membrane peeling is an effective method for the treatment of patients with idiopathic epiretinal membrane.